Kidney supportive care: an update of the current state of the art of palliative care in CKD patients - Tavares,Alze Pereira dos Santos (2021)
ABSTRACT Chronic kidney disease (CKD) has become a public health burden worldwide for its increasing incidence and prevalence, high impact on the health related quality of life (HRQoL) and life expectancy, and high personal and social cost. Patients with advanced CKD, in dialysis or not, suffer a burden from symptoms very similar to other chronic diseases and have a life span not superior to many malignancies. Accordingly, in recent years, renal palliative care has been recommended to be integrated in the traditional care delivered to this population. This research provides an updated overview on renal palliative care from the relevant literature.